Desulfurization adsorbent and preparation method and application thereof

By using small-pore SB powder, modified kaolin and zirconia composite carriers, combined with metal components such as zinc, nickel and lanthanum, an efficient desulfurization adsorbent was prepared, which solved the problem of poor desulfurization effect of heavy oils in the prior art and achieved efficient and stable desulfurization effect.

CN116408042BActive Publication Date: 2025-04-01PETROCHINA CO LTD
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN202111642375.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-04-01
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

The existing desulfurization agents have limited effects in the desulfurization treatment of heavy oils, and their performance such as strength, desulfurization activity and stability need to be further improved.

Method used

A highly efficient desulfurization adsorbent is prepared by combining small-pore SB powder, modified kaolin and zirconia with metal components such as zinc, nickel and lanthanum. Through multi-step synergistic reaction, the adsorption capacity of sulfur components in heavy oils is significantly improved.

Benefits of technology

The desulfurization adsorbent exhibits a desulfurization rate of up to 80%, and has good mechanical properties and stability. It can be regenerated and used multiple times, and is suitable for deep desulfurization treatment of heavy oils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003442824700000231
    Figure BDA0003442824700000231
  • Figure HDA0003442824710000011
    Figure HDA0003442824710000011
  • Figure HDA0003442824710000021
    Figure HDA0003442824710000021
Patent Text Reader

Abstract

The present invention provides a desulfurization adsorbent and a preparation method and application thereof, wherein the desulfurization adsorbent comprises a carrier, a first metal component and a second metal component; wherein the first metal component comprises zinc and nickel, the second metal component comprises lanthanum, the carrier is compounded from raw materials containing small-pore SB powder, modified kaolin and zirconium oxide, the pore volume of the small-pore SB powder is not greater than 0.8 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is subjected to a primary roasting at 900°C to 1100°C, then subjected to alkali modification, then washed to neutrality, and then subjected to a secondary roasting at 500°C to 600°C to obtain the modified kaolin. The desulfurization adsorbent of the present invention has the advantages of high strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides a desulfurization adsorbent and a preparation method and application thereof, belonging to the field of oil desulfurization treatment. Background Art

[0002] With the improvement of environmental protection requirements, low-sulfur clean oil products have received extensive attention. For example, the International Maritime Organization (IMO) stipulates that the sulfur content of global marine fuel shall not exceed 0.5wt% from January 2020, which puts forward a more urgent demand for the development of low-sulfur fuel. In addition, desulfurization of heavy oil such as residual oil and converting it into low-sulfur clean oil products as a blending component of fuel oil and other oil products is an important way to achieve efficient utilization of heavy oil.

[0003] Hydrodesulfurization and adsorption desulfurization are common means to achieve the purpose of oil desulfurization. For example, patent document CN111672534A discloses a hydrocracking catalyst for hydrocracking of heavy oil to reduce secondary cracking of cracking products; CN112742369A discloses a catalyst composition and its application and a method for selective desulfurization of mercaptans for removing mercaptans from oil products; CN101491764A discloses a residual oil hydrogenation catalyst for hydrodemetallization, hydrodesulfurization and hydroremoval of residual carbon in residual oil. and hydrogenation conversion; CN105582941A discloses a desulfurization catalyst and a preparation method thereof and a method for desulfurizing hydrocarbon oil, which can be used for desulfurization of cracked gasoline and diesel engine dyes; CN108212077A discloses a gasoline adsorption desulfurizer, including ethanol, attapulgite, zinc oxide, and triethylenediamine, which is used for adsorption desulfurization of gasoline; CN103642520A discloses a preparation and application method of an adsorption desulfurizer for catalytic cracking gasoline modification, which first prepares ZnO / ZS M-5 core-shell structure composite material, and then the composite material is mixed evenly with lithium hydroxide dry glue powder and diatomaceous earth, and an acidic glue solvent solution is added thereto, and then extruded and calcined in sequence to obtain a core-shell type ZnO / ZSM-5 adsorption desulfurizer, which is used for the modification of catalytic cracking gasoline with a sulfur content of less than 150ppm; CN104056632A discloses a fuel oil deep adsorption desulfurization catalyst and its preparation method and application, which has a good desulfurization effect on catalytic cracking gasoline; CN1019051 61A discloses a catalytic cracking gasoline adsorption desulfurization catalyst and its preparation and application, which is used for the desulfurization treatment of catalytic cracking gasoline; CN102188954A discloses an activated carbon for adsorbing and removing sulfides in gasoline and its preparation method, which is used for the adsorption desulfurization of gasoline; CN105771892A discloses an oil desulfurizer and its desulfurization method, which mixes adsorbents with strong adsorption capacity such as molecular sieve, activated carbon, activated coke, natural zeolite, kaolin, bentonite, etc. to form a composite adsorbent;

[0004] Desulfurizer is an important factor affecting the desulfurization effect. Optimizing the structure and performance of desulfurizer is an effective means to improve the desulfurization effect. Although there have been studies and reports on desulfurizers such as hydrodesulfurizers and desulfurizers, on the one hand, the strength, desulfurization activity, stability and desulfurization efficiency of desulfurizers at this stage need to be further improved. On the other hand, the current desulfurizers are mostly used for the desulfurization of light oils such as gasoline, kerosene and diesel, but have limited desulfurization effects on heavy oils. It is urgent to develop effective desulfurizers suitable for the desulfurization of heavy oils. Summary of the invention

[0005] The present invention provides a desulfurization adsorbent and a preparation method and application thereof, which has the advantages of high adsorbent strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil, effectively overcoming the defects of the prior art.

[0006] In one aspect of the present invention, a desulfurization adsorbent is provided, comprising a carrier, a first metal component and a second metal component; wherein the first metal component comprises zinc and nickel, the second metal component comprises lanthanum, the carrier is compounded from raw materials containing small-pore SB powder, modified kaolin and zirconium oxide, the pore volume of the small-pore SB powder is not greater than 0.8 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is once calcined at 900°C to 1100°C, then alkali-modified, then washed to neutral, and then calcined for a second time at 500°C to 600°C to obtain the modified kaolin.

[0007] According to one embodiment of the present invention, based on the oxide of the first metal component and the oxide of the second metal component, the following conditions are satisfied: the mass of the first metal component accounts for 50% to 80% of the sum of the masses of the carrier and the first metal component; and / or the mass of nickel in the first metal component accounts for 3% to 12% of the sum of the masses of the carrier and the first metal component; and / or the mass of the second metal component accounts for 0.5% to 8% of the sum of the masses of the carrier and the first metal component.

[0008] According to one embodiment of the present invention, the mass ratio of the small-pore SB powder to the modified kaolin is 1:(1-3); and / or, the mass ratio of the zirconium oxide to the small-pore SB powder is (0.5-1):1; and / or, the pore volume of the small-pore SB powder is 0.4 mL / g-0.8 mL / g, and the specific surface area is 180 m 2 / g~260m 2 / g, the peptization index is greater than 97%.

[0009] According to one embodiment of the present invention, the time of the first calcination is 2h to 5h; and / or, the temperature of the first calcination is 950°C to 1050°C; and / or, the process of alkali modification includes: immersing the kaolin raw material in an inorganic alkali solution for modification, the mass concentration of the inorganic alkali solution is 5% to 20%, and the mass ratio of the inorganic alkali solution to the kaolin raw material is (2 to 4):1; the time of the alkali modification is 1h to 6h; and / or, the time of the secondary calcination is 2h to 5h.

[0010] In another aspect of the present invention, a method for preparing the above-mentioned desulfurization adsorbent is provided, comprising: (I) adding inorganic acid and water to a mixture containing the small-pore SB powder, modified kaolin, zirconium oxide, a binder and zinc oxide, and then sequentially performing molding, drying and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a third intermediate; (IV) modifying the third intermediate with trifluoroacetic acid, and then drying and calcining to obtain an adsorbent precursor; (V) subjecting the adsorbent precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain the desulfurization adsorbent.

[0011] According to one embodiment of the present invention, the binder includes at least one of sodium methyl cellulose, sodium carboxymethyl starch, sodium carboxymethyl cellulose, and sesbania powder; and / or, the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 1% to 7% of the sum of the mass of the small pore SB powder, modified kaolin, zirconium oxide, zinc oxide and the nickel compound; and / or, the mass ratio of the inorganic acid to the small pore SB powder is (0.5 to 1): 1; and / or, the zinc oxide includes nano zinc oxide powder with a particle size of not more than 100 nm; and / or, the calcination conditions in step (I) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, the calcination conditions in step (II) are : the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, the calcination conditions in step (III) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, in step (IV), the process of modifying the third intermediate with trifluoroacetic acid comprises: impregnating the third intermediate with a solution containing the trifluoroacetic acid, and the mass ratio of the trifluoroacetic acid to the third intermediate is (0.01 to 0.1):1; and / or, the calcination conditions in step (IV) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, in step (V), the volume space velocity of the hydrogen is 500h -1~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h.

[0012] In another aspect of the present invention, a method for desulfurization of sulfur-containing oil is provided, comprising: using the above-mentioned desulfurization adsorbent to desulfurize the sulfur-containing oil; or, preparing the desulfurization adsorbent according to the above-mentioned preparation method, and using the prepared desulfurization adsorbent to desulfurize the sulfur-containing oil.

[0013] According to one embodiment of the present invention, the temperature of the desulfurization treatment is 300°C to 550°C; and / or, the pressure of the desulfurization treatment is 0.5MPa to 10MPa; and / or, the feed space velocity of the sulfur-containing oil product is 0.1h -1 ~1.0h -1 ; and / or, the desulfurization treatment is carried out under a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):1.

[0014] According to one embodiment of the present invention, the method further comprises: obtaining a desulfurized oil product and a regenerated adsorbent after the desulfurization treatment; regenerating the regenerated adsorbent to obtain a regenerated adsorbent; and returning the regenerated adsorbent to the desulfurization treatment; wherein the regeneration treatment comprises: subjecting the regenerated adsorbent to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000h / min. -1 ~3000h -1 The temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5 MPa, and the time of the oxidation regeneration is 20h to 100h; the regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated adsorbent; wherein the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300° C. to 500° C., the pressure of the second reduction treatment is 0 to 3 MPa, and the time of the second reduction treatment is 1 h to 6 h.

[0015] According to one embodiment of the present invention, the sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0016] The desulfurization adsorbent provided by the present invention has the advantages of good mechanical properties, long service life, good desulfurization activity, etc., can significantly improve the desulfurization rate, and has a wide range of applications. It is particularly suitable for the desulfurization treatment of heavy oil, effectively removes sulfides such as thiophenes, and realizes the deep desulfurization of sulfur-containing oil products such as heavy oil. At the same time, it can also reduce the viscosity of the oil products and improve the quality of the oil products after desulfurization. The oil products after desulfurization can be used as clean gasoline blending components or other purposes. Studies have shown that the breaking strength of the desulfurization adsorbent is as high as 30N or more, showing good mechanical properties, good structural stability, and is easy to use; the desulfurization rate of heavy oil is as high as 80% or more, and the desulfurization adsorbent can still achieve a good desulfurization rate after regeneration 1 to 60 times or even higher times, showing good activity stability and long service life. In addition, the raw materials of the desulfurization adsorbent of the present invention are cheap and easy to obtain, and it also has the advantages of low cost, simple preparation process, and simple desulfurization process using the desulfurization adsorbent, mild conditions, and high efficiency, which is of great significance for practical industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD spectra of the adsorbent precursors during the preparation of fresh desulfurization adsorbents S1, S2, D4, and D5 (the abscissa is the 2θ angle (Theta), and the ordinate is the peak intensity (intensity));

[0018] Figure 2 This is the XRD spectrum of the regenerated adsorbent precursor during the regeneration process of the regenerated adsorbent produced after desulfurization treatment of S1, S2, D4, and D5. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only descriptions of the principles and features of the present invention. The examples cited are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the present invention, terms such as "first" and "second" are only used for descriptive purposes, such as distinguishing between components, etc., to more clearly illustrate / explain the technical scheme, and cannot be understood as indicating or implying the number of technical features indicated or the order of substantial significance.

[0020] The desulfurization adsorbent of the present invention comprises: a carrier, a first metal component and a second metal component; wherein the first metal component comprises zinc and nickel, the second metal component comprises lanthanum, the carrier is compounded from raw materials containing small-pore SB powder, modified kaolin and zirconium oxide, the pore volume of the small-pore SB powder is not greater than 0.8 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is once calcined at 900°C to 1100°C, then alkali-modified, then washed to neutrality, and then calcined twice at 500°C to 600°C to obtain the modified kaolin.

[0021] After research and analysis, the inventors believe that, in the desulfurization adsorbent composition system of the present invention, the first metal component serves as the main active component for sulfur adsorption / absorption. During the desulfurization treatment of the oil product, the sulfur element in the oil product is captured by the nickel component to form nickel sulfide. The nickel sulfide reacts with the zinc component to form zinc sulfide. The second metal component, as an active metal, can promote the sulfur transfer and other processes. Thus, through multi-step coordinated reactions, the sulfur component in the oil product is adsorbed in the desulfurization adsorbent in the form of metal sulfides such as zinc sulfide, thereby achieving the purpose of desulfurization.

[0022] Generally speaking, when using conventional alumina-based carriers and desulfurization adsorbents with zinc oxide and nickel as the main adsorption active components for heavy oil adsorption desulfurization, there are at least the following problems: first, due to the inherent properties of ZnO as the main adsorption component, the strength of the adsorbent is poor; second, the adsorption active components (such as ZnO) and the carrier Al 2 O 3 There is a strong interaction between them. Zinc silicate and zinc aluminate are easily formed during the adsorption desulfurization reaction, adsorbent regeneration and other cyclic processes, which makes some adsorption active components such as ZnO lose the ability to desulfurize and store sulfur, thereby gradually inactivating the desulfurization adsorbent. At the same time, it will also reduce the strength of the adsorbent, affecting the desulfurization performance and service life of the adsorbent.

[0023] According to the research of the present invention, the above-mentioned carrier composed of small-pore SB powder, modified kaolin and zirconium oxide is used to match the above-mentioned first metal component and the second metal component to form a desulfurization adsorbent, which can effectively solve the above-mentioned problems. The inventor believes through research and analysis that in the preparation process of modified kaolin, silicon aluminum spinel and silicon oxide can be produced by roasting, and silicon oxide can be extracted through the alkali modification process, thereby reducing the content of active silicon oxide in kaolin, thereby reducing the amount of zinc silicate produced by silicon oxide and zinc oxide in the desulfurization treatment process using the desulfurization adsorbent. At the same time, kaolin The clay raw material generates silica-alumina spinel during the roasting process, which can also reduce the amount of zinc aluminate generated during the desulfurization treatment using a desulfurization adsorbent, thereby improving the desulfurization activity and stability of the desulfurization adsorbent. The addition of zirconium oxide to the carrier can increase the dispersion of the active components of the adsorbent, weaken the interaction between aluminum oxide and zinc oxide, and effectively inhibit the generation of inactive components such as zinc aluminate, especially the generation of inactive components such as zinc aluminate during the adsorbent reaction regeneration process, further ensuring the strength and stability of the adsorbent, facilitating its recycling and regeneration, and increasing its service life.

[0024] For example, the primary calcination temperature may be 900° C., 950° C., 1000° C., 1050° C., 1000° C., or a range consisting of any two thereof, preferably 950° C. to 1050° C. In addition, the primary calcination time may be 2 h to 5 h, such as 2 h, 3 h, 4 h, 5 h, or a range consisting of any two thereof, preferably 3 h to 4 h.

[0025] In the preparation process of the modified kaolin, an inorganic base can be used for alkali modification. Preferably, the inorganic base includes an alkali metal hydroxide, such as sodium hydroxide. In some embodiments, the alkali modification process includes: immersing the kaolin raw material in an inorganic alkali solution for modification, the mass concentration of the inorganic alkali solution is 5% to 20%, such as 5%, 8%, 10%, 12%, 15%, 18%, 20% or any two of them, preferably 10% to 15%; the mass ratio of the inorganic alkali solution to the kaolin raw material is (2 to 4): 1, such as 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1 or any two of them, preferably (2.5 to 3.5): 1. In addition, the time for the alkali modification can generally be 1h to 6h, such as 1h, 2h, 3h, 4h, 5h, 6h or any two of them, preferably 3h to 4h.

[0026] In the process of preparing modified kaolin, after alkali modification, the obtained alkali-modified product can be repeatedly filtered and washed until neutral, and then subjected to secondary calcination. Exemplarily, the temperature of the secondary calcination can be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, or a range consisting of any two thereof. The time of the secondary calcination can generally be 2h to 5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or a range consisting of any two thereof.

[0027] In the present invention, the carrier is compounded by small-pore SB powder, modified kaolin and zirconium oxide. To further optimize the performance of the adsorbent, the pore volume of the small-pore SB powder can be 0.4 mL / g to 0.8 mL / g, for example, 0.5 mL / g, 0.5 mL / g, 0.6 mL / g, 0.7 mL / g, 0.8 mL / g or any two thereof. The specific surface area of ​​the small-pore SB powder can be 180 m 2 / g~260m 2 / g, for example 180m 2 / g, 200m 2 / g, 220m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g or any two of them, the peptization index of the small-pore SB powder is greater than 97%. In the specific implementation, the purity of the small-pore SB powder used is greater than 99.9%.

[0028] In addition, the mass ratio of small pore SB powder to modified kaolin can be 1:(1-3), such as 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or any two thereof. The mass ratio of zirconium oxide to small pore SB powder can be (0.5-1):1, such as 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or any two thereof.

[0029] In the above-mentioned desulfurization adsorbent, the mass percentage of the first metal component serving as the sulfur absorption unit is generally not lower than (i.e. equal to or greater than) the mass percentage of the carrier. In some preferred embodiments, calculated as the oxide of the first metal component, the mass of the first metal component accounts for 50% to 80% of the sum of the masses of the carrier and the first metal component, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80% or the range consisting of any two thereof, and the mass of the carrier accounts for 20% to 50% of the sum of the masses of the carrier and the first metal component, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50% or the range consisting of any two thereof.

[0030] In general, the mass percentage of zinc in the first metal component is preferably higher than the mass percentage of nickel, calculated as the oxide of the first metal component. In some embodiments, the mass of nickel in the first metal component accounts for 3% to 12% of the sum of the mass of the support and the first metal component, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or a range consisting of any two thereof, calculated as the oxide of the first metal component.

[0031] In addition, in some embodiments, the mass of the second metal component, calculated as the oxide of the first metal component and the oxide of the second metal component, accounts for 0.5% to 8% of the sum of the masses of the carrier and the first metal component, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or a range consisting of any two of them.

[0032] In the above-mentioned desulfurization adsorbent, the first metal component and the second metal component are loaded on a carrier. Generally, most of the metal components exist in the form of oxides (such as zinc exists in the form of zinc oxide), wherein at least part of the nickel can be present in a reduced state (i.e., in the form of nickel element). In specific implementation, the compounds of each metal component (such as metal oxides and / or metal salts, etc.) can be used to load each metal component on the carrier through an impregnation method. After the loading of each metal component is completed, the obtained adsorbent precursor is subjected to a first reduction treatment in an atmosphere containing hydrogen, so that the nickel component therein is at least partially reduced to nickel element, thereby preparing a desulfurization adsorbent and improving its desulfurization activity.

[0033] The above-mentioned carrier can be specifically prepared by compounding raw materials containing small-pore SB powder, modified kaolin, zirconium oxide and a binder, and its preparation process can include: mixing small-pore SB powder, modified kaolin, zirconium oxide, a binder with an inorganic acid and water, and then drying and calcining to form a carrier. The metal component can be introduced during the preparation of the carrier, or the metal component can be impregnated after the carrier is prepared.

[0034] In a preferred embodiment of the present invention, the preparation method of the above-mentioned desulfurization adsorbent includes: (I) adding inorganic acid and water to a mixture containing small pore SB powder, modified kaolin, zirconium oxide, a binder and zinc oxide, and then sequentially forming, drying and calcining to obtain a first intermediate; (II) using a first impregnation solution containing a nickel compound to impregnate the first intermediate, and drying and calcining the impregnation product to obtain a second intermediate; (III) using a second impregnation solution containing a compound of a second metal component to impregnate the second intermediate, and drying and calcining the impregnation product to obtain a third intermediate; (IV) using trifluoroacetic acid to modify the third intermediate, and then drying and calcining to obtain an adsorbent precursor; (V) subjecting the adsorbent precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain a desulfurization adsorbent.

[0035] In the above preparation process, zinc oxide, a binder, and carrier raw materials such as small-pore SB powder, modified kaolin, and zirconium oxide are first mixed and formed, and then the nickel compound and the second metal component are sequentially impregnated by an impregnation method, which can improve the strength and desulfurization activity of the prepared desulfurization adsorbent. The inventor believes through research and analysis that in the above preparation process, after the drying and calcination treatments of steps (I) to (IV), the small-pore SB powder, modified kaolin, and zirconium oxide are compounded to form a carrier, and the binder gradually volatilizes during the calcination process, thereby forming a pore structure in the prepared adsorbent, and the compounds of each metal component are basically converted into metal oxides; after the first reduction treatment of step (V), the nickel therein can be basically present in a reduced state, while other metal components (such as zinc, the second metal component and the third metal component) are usually still present in the form of metal oxides, thereby a desulfurization adsorbent with suitable composition and structure can be prepared, which is suitable for the desulfurization treatment of heavy oil, and can show good adsorption desulfurization activity, stability and mechanical properties, and improve the desulfurization rate and service life.

[0036] In addition, according to the research of the present invention, under the above-mentioned preparation system, the trifluoroacetic acid modification treatment in step (IV) can improve the acidity and other properties of the prepared desulfurization adsorbent, increase the reaction activity of the CS bond and the CN bond in the oil product during the desulfurization treatment, and improve the desulfurization activity and denitrification activity of the desulfurization adsorbent, thereby achieving the purpose of desulfurization and denitrification of sulfur-containing and nitrogen-containing oil products such as heavy oil. Studies have shown that when the desulfurization adsorbent is used to treat sulfur-containing and nitrogen-containing oil products such as heavy oil, the desulfurization rate can reach more than 80%, and the denitrification rate can reach more than 50%.

[0037] Specifically, in the above preparation process, the first metal component compound includes zinc oxide and nickel compound, and the second metal component compound includes lanthanum compound. In general, the content of each metal component in the prepared adsorbent can be regulated by the amount of raw materials such as each metal component compound, and the amount of each raw material is as follows: based on the oxide of each metal component (such as nickel compound based on nickel oxide, lanthanum compound based on lanthanum oxide), the mass of the first metal component compound accounts for 50% to 80% of the sum of the mass of the carrier and the first metal component compound, the mass of the nickel compound accounts for 3% to 12% of the sum of the mass of the carrier and the first metal component compound, the mass of the second metal component compound accounts for 0.5% to 8% of the sum of the mass of the carrier and the first metal component compound, the mass ratio of small pore SB powder to modified kaolin is 1: (1 to 3), and the mass ratio of zirconium oxide to small pore SB powder is (0.5 to 1): 1.

[0038] In step (I), the mixture can be a wet mixture, a paste mixture, a kneaded body or a slurry, etc., and the molding process can be oil-ammonia column molding, oil-water column molding, oil column molding, rolling ball molding or extrusion ball molding, etc., preferably extrusion ball molding, wherein the amount of water used can be convenient for molding, for example, it can meet the extrusion ball molding, and there is no particular restriction on this. Through the above molding process, the first intermediate formed can be spherical and / or toothed ball-shaped, and the particle diameter of the first intermediate is preferably 1.5mm to 3mm, for example, 1.5mm, 2mm, 2.5mm, 3mm or the range composed of any two thereof.

[0039] In step (I), the zinc oxide may include nano-sized particles of zinc oxide, preferably nano zinc oxide powder with a particle size of no more than 100 nm. In specific implementation, the purity of the zinc oxide used is greater than 96%.

[0040] In step (I), the binder may include at least one of sodium methyl cellulose, sodium carboxymethyl starch, sodium carboxymethyl cellulose, and sesbania powder. In addition, the amount of the binder can generally be controlled as follows: the mass of the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 1% to 7% of the sum of the mass of the small pore SB powder, modified kaolin, zirconium oxide, zinc oxide and the nickel compound, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7% or a range consisting of any two of them.

[0041] In some embodiments, in step (I), the mass ratio of the inorganic acid to the small-pore SB powder is (0.5-1):1, such as 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or any two thereof. It should be noted that the mass ratio of the inorganic acid to the small-pore SB powder is calculated based on the inorganic acid without solvents such as water. In the specific implementation, inorganic acid solutions of different concentrations may be used, and the mass of the inorganic acid therein can be converted according to its concentration to control the mass ratio of the inorganic acid (non-solution) to the small-pore SB powder to be (0.5-1):1. Preferably, the inorganic acid comprises nitric acid.

[0042] In step (II), the first impregnation solution may be a solution or suspension containing a nickel compound, and the nickel compound may particularly include a soluble nickel compound (e.g., a water-soluble nickel compound). The first impregnation solution is a solution prepared by dissolving a soluble nickel compound in water. The soluble nickel compound may include, for example, a soluble nickel salt, preferably nickel nitrate and / or nickel acetate. The soluble nickel salt may be in the form of a hydrate without or with water of crystallization, and the present invention is not particularly limited to this.

[0043] In specific implementation, in step (II), the impregnation can be carried out by an equal volume impregnation method. In some embodiments, in step (II), the impregnation temperature is 20°C to 90°C, such as 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof, and the impregnation time is 1h to 24h, such as 1h, 5h, 10h, 15h, 20h, 24h or any two thereof; the mass ratio of the first impregnation liquid to the first intermediate is (1 to 5): 1, such as 1: 1, 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1, 5: 1 or any two thereof.

[0044] In step (III), the second impregnation solution may be a solution or a suspension. Preferably, the compound of the second metal component includes a soluble compound of the second metal component (generally a water-soluble compound). The second impregnation solution is a solution prepared by dissolving the soluble compound of the second metal component in water. The compound of the second metal component may specifically include a soluble salt of the second metal component (i.e., a soluble salt of lanthanum), preferably a nitrate of the second metal component (i.e., lanthanum nitrate).

[0045] In specific implementation, in step (III), the impregnation can be carried out by an equal volume impregnation method. In some embodiments, in step (III), the impregnation temperature is 20°C to 90°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof, preferably 40 to 65°C, and the impregnation time is 1h to 24h, for example, 1h, 5h, 10h, 15h, 20h, 24h or any two thereof; the mass ratio of the second impregnation liquid to the second intermediate is (1 to 5): 1, for example, 1: 1, 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1, 5: 1 or any two thereof.

[0046] In step (IV), the third intermediate can be modified by an impregnation method, and specifically, the third intermediate can be impregnated with a solution containing trifluoroacetic acid to achieve modification of the third intermediate; wherein the mass ratio of trifluoroacetic acid to the third intermediate can generally be (0.01 to 0.1):1, for example, 0.01:1, 0.03:1, 0.06:1, 0.08:1, 0.1:1 or a range consisting of any two thereof, and the mass ratio of the solution containing trifluoroacetic acid to the third intermediate is (1 to 3):1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or a range consisting of any two thereof, and the solution containing trifluoroacetic acid can specifically be an aqueous solution of trifluoroacetic acid.

[0047] Optionally, the drying process in step (I), step (II), step (III), and step (IV) independently comprises: first drying at 20°C to 30°C (such as room temperature) for 12h to 48h, then drying at 60°C to 120°C (preferably 80°C to 110°C) for 3h to 24h (preferably 6h to 10h), and then calcining the obtained dried product. The drying temperature, drying time and other conditions in step (I), step (II), step (III), and step (IV) may be the same or different.

[0048] In addition, the calcination conditions in step (I), step (II), step (III), and step (IV) can be independently: the calcination temperature is 400°C to 700°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or a range consisting of any two thereof, preferably 450°C to 650°C, and the calcination time is 1h to 10h, such as 1h, 3h, 5h, 7h, 10h, or a range consisting of any two thereof, preferably 3h to 5h. Among them, the calcination temperature, calcination time and other conditions in step (I), step (II), step (III), and step (IV) can be the same or different.

[0049] In step (V), hydrogen can be introduced into the system to contact the adsorbent precursor with hydrogen to perform the first reduction treatment. The volume space velocity of hydrogen can be 500h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 , 2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, in step (V), the volume fraction of hydrogen in the atmosphere containing hydrogen is 50% to 100%, such as 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, and the remainder is, for example, an inert gas.

[0050] In addition, in step (V), the temperature of the first reduction treatment process can be 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof, preferably 350°C to 450°C, the pressure of the first reduction treatment process is 0 to 3MPa, for example, 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or a range consisting of any two thereof, preferably 0.5 to 1.5MPa, and the time of the first reduction treatment is 1h to 6h, for example, 1h, 2h, 3h, 4h, 5h, 6h or a range consisting of any two thereof, preferably 2h to 4h.

[0051] In the present invention, unless otherwise specified, the masses of raw materials such as small pore SB powder, kaolin, zirconium oxide, zinc oxide, etc. are calculated on a dry basis.

[0052] In one embodiment of the present invention, a method for adsorption desulfurization of sulfur-containing oil is provided, comprising: using the above-mentioned desulfurization adsorbent to desulfurize the sulfur-containing oil; or, preparing the desulfurization adsorbent according to the above-mentioned preparation method, and using the prepared desulfurization adsorbent to desulfurize the sulfur-containing oil.

[0053] In some embodiments, the temperature of the desulfurization treatment can be 300°C to 550°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or a range consisting of any two thereof, preferably 400-450°C; the pressure of the desulfurization treatment is 0.5MPa to 10MPa, for example, 0.5MPa, 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa or a range consisting of any two thereof, preferably 3MPa to 7MPa; the feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 , for example 0.1h -1 、0.3h -1 、0.5h -1 , 0.8h -1 , 1h -1 Or a range consisting of any two of them.

[0054] In some embodiments, the desulfurization treatment is carried out in a hydrogen atmosphere, that is, the sulfur-containing oil and the desulfurization adsorbent are contacted and reacted in a hydrogen atmosphere to carry out the desulfurization treatment. The volume ratio of hydrogen to the sulfur-containing oil (hydrogen-to-oil volume ratio) is (100-800):1, such as 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1 or a range consisting of any two of them.

[0055] In some embodiments, the above desulfurization process further includes: obtaining desulfurized oil and regenerated adsorbent after desulfurization treatment; regenerating the regenerated adsorbent to obtain regenerated adsorbent; and returning the regenerated adsorbent for desulfurization treatment.

[0056] The regeneration process comprises: subjecting the regenerated adsorbent to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of them, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , for example 1000h -1 , 1300h -1 、1500h -1 , 1800h -1 , 2000h -1 , 2300h -1 、2500h -1 、2800h -1 、3000h -1or a range consisting of any two thereof; the temperature of the oxidation regeneration is 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof; the pressure of the oxidation regeneration is 0 to 0.5 MPa; the time of the oxidation regeneration is 20h to 100h; the regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated adsorbent; wherein the temperature of the second reduction treatment ... 0℃, 450℃, 500℃ or any two of them in the range, preferably 350~450℃, the pressure of the second reduction treatment is 0~3MPa, for example 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or any two of them in the range, preferably 0.5~1.5MPa, the time of the second reduction treatment is 1h~6h, for example 1h, 2h, 3h, 4h, 5h, 6h or any two of them in the range, preferably 2h~4h. In the present invention, unless otherwise specified, the pressures are all gauge pressures.

[0057] In a specific implementation, hydrogen can be introduced into the system to contact the regenerated adsorbent precursor with hydrogen to perform the second reduction treatment. The volume space velocity of hydrogen can be 500 h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 , 2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, during the second reduction treatment, the volume fraction of hydrogen in the hydrogen-containing atmosphere is 10% to 100%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, preferably 60% to 100%, and the remainder may be an inert gas or oil gas such as methane.

[0058] Specifically, the above desulfurization treatment is carried out in a reactor, and the reactor may include a fixed bed reactor and / or a moving bed reactor. Taking the fixed bed reactor as an example, in specific implementation, the desulfurization adsorbent may be loaded in the fixed bed reactor, and then the sulfur-containing oil product enters the fixed bed reactor, contacts and reacts with the desulfurization adsorbent therein, and obtains the desulfurized oil product and the regenerated adsorbent respectively; after the regenerated adsorbent is subjected to the above regeneration treatment, it is returned to the fixed bed reactor to form a cycle.

[0059] In the present invention, the above-mentioned desulfurization adsorbent is used to remove small molecular sulfides and large molecular sulfides in sulfur-containing oil products, and has a wide range of applications. Generally, the sulfides in the above-mentioned sulfur-containing oil products include at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, but are not limited thereto. Exemplarily, thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene. The present invention can efficiently remove these sulfides in sulfur-containing oil products, especially large molecular sulfides such as thiophenes, thereby achieving deep desulfurization of sulfur-containing oil products and reducing the total sulfur content of the desulfurized oil products.

[0060] Generally speaking, the equivalent double bond value (DBE) of sulfides in heavy oil is distributed between 9 and 16. 22 -C 46 , mainly benzothiophene, dibenzothiophene, benzonaphthothiophene and other macromolecular sulfides, which are difficult to remove, and the asphaltene and colloid particles in the heavy oil are large, which are easy to block the catalyst pores, causing problems such as catalyst deactivation. The desulfurization adsorbent of the present invention can efficiently remove sulfides in heavy oil, and has good activity and stability, can be regenerated and used multiple times, and maintains good desulfurization efficiency. In some specific embodiments, the above-mentioned sulfur-containing oil includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0061] In the present invention, the above-mentioned desulfurization adsorbent is used to desulfurize sulfur-containing oil products, which can improve the desulfurization efficiency, and at the same time can also improve the denitrification rate and reduce the viscosity of the desulfurized oil products, thereby improving the comprehensive quality of the desulfurized oil products. The present invention can also achieve efficient desulfurization, denitrification and viscosity reduction for sulfur-containing oil products with high sulfur content, high nitrogen content and high viscosity (such as the above-mentioned heavy oil). Taking heavy oil with a sulfur content of about 2.3wt% and a nitrogen content of about 0.8wt% (such as vacuum residue) as an example, through the above-mentioned desulfurization process, the desulfurization rate can reach more than 80%, and the denitrification rate can reach more than 50%.

[0062] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0063] In the following embodiments, the relevant performance testing process is as follows:

[0064] (1) With reference to the standard "SH / T 0689-2000", the total sulfur and total nitrogen content in the liquid oil sample was determined by ultraviolet fluorescence / chemiluminescence method at a temperature of 1000°C, argon gas of 30 psi, and oxygen of 10 psi. According to this method, the mass percentage of total sulfur in the heavy oil raw material was determined, x 0 and the mass percentage of total sulfur in the desulfurized oil x 1 , according to w=(x 0 -x 1 ) / x 0 Calculate the desulfurization rate w; According to this method, the mass percentage of total nitrogen in the heavy oil raw material y is determined respectively 0 and the mass percentage of total nitrogen in desulfurized oil 1 , according to z=(y 0 -y 1 ) / y 0 Calculate the denitrification rate z.

[0065] (2) A universal automatic strength tester is used to measure the mechanical strength of the molded particles (such as S1 to S6, D1 to D6 below). The instrument range is 0 to 500 N, and the accuracy is 0.1 N. The measurement process is as follows: a single sample is placed between two rigid platforms, one of which remains stationary and the other moves axially downward at a very low speed to produce extrusion friction on the particles. The fracture strength (or crushing strength) is determined as the maximum load measured before the particles break. According to this process, 50 regular particles are selected for each sample to perform a crushing strength test, so as to obtain representative mechanical properties.

[0066] (3) With reference to the standard GB / T 265-1988 Determination of kinematic viscosity and calculation of dynamic viscosity of petroleum products, the time for a certain volume of liquid (such as the heavy oil feedstock and desulfurized oil product described below) to flow through a calibrated glass capillary viscometer under gravity is measured at a constant temperature of 40°C. The kinematic viscosity of the liquid at this temperature is determined by multiplying the capillary constant of the viscometer by the movement time. According to this process, each liquid sample is measured twice, and the average value is taken to obtain the liquid viscosity.

[0067] (4) The crystal structure of each adsorbent sample was characterized by X-ray diffraction (XRD) analysis. Specifically, the XRD analysis was performed using a Rigaku D / max 2200PC X-ray powder diffractometer under the conditions of Cu target, graphite monochromator, scanning speed of 10 degrees / min, scanning step of 0.02 degrees, voltage of 40 kV, and current of 20 mA. The intensity and position of the diffraction peaks in the measured XRD spectrum were qualitatively analyzed to determine the composition of the adsorbent (including the type of substance, structure, crystalline state, and state of element existence, etc.).

[0068] In the following examples, small-pore SB powder was purchased from Suzhou Baird New Material Technology Co., Ltd., model number YH-2, and the pore volume of the small-pore SB powder was 0.58 mL / g, and the specific surface area was 214 m 2 / g, the peptization index is greater than 97%; kaolin is purchased from China Kaolin Co., Ltd.; other reagents are purchased from Aladdin Reagent Network; the zinc oxide used is nano zinc oxide powder with a particle size of no more than 100nm.

[0069] In the following examples and comparative examples, modified kaolin was prepared according to the following process: 2000 g of kaolin raw material was calcined at 1000° C. for 3 h, then modified in 6000 g of 10% sodium hydroxide solution for 3 h, then filtered and washed several times until neutral, and then calcined at 550° C. for 3 h to obtain modified kaolin.

[0070] Example 1

[0071] (1) 71 g of small-pore SB powder, 72 g of modified kaolin, 57 g of zirconium oxide, 70 g of sodium carboxymethyl cellulose and 770 g of zinc oxide powder were mixed evenly, 430 g of water and 71 g of nitric acid were added, and the mixture was mixed evenly and then extruded into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 24 hours, then dried at 100° C. for 8 hours, and then calcined at 550° C. for 4 hours to obtain a first spherical intermediate;

[0072] (2) Weighing 100 g of nickel acetate tetrahydrate, adding 3900 g of water to prepare a first impregnation solution; placing the first intermediate in the first impregnation solution, and impregnating at 50° C. for 8 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 80° C. for 10 h, and then calcining at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0073] (3) Weigh 106 g of lanthanum nitrate and add 3800 g of water to prepare a second impregnation solution; place the second intermediate in the second impregnation solution and impregnate at 60° C. for 6 h; dry the obtained impregnation product at room temperature for 12 h, then dry it at 110° C. for 6 h, and then calcine it at 600° C. for 3 h to obtain a spherical third intermediate;

[0074] (4) Weigh 60 g of trifluoroacetic acid, add 1500 g of water to prepare a solution, place the third intermediate in the solution, and immerse it at 60° C. for 6 hours; dry the obtained impregnation product at room temperature for 12 hours, then dry it at 110° C. for 6 hours, and then calcine it at 600° C. for 3 hours to obtain an adsorbent precursor;

[0075] (5) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S1; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0076] Among them, the first metal component (zinc + nickel) and the second metal component (lanthanum) are both calculated as metal oxides, the mass of the first metal component accounts for 80% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 3% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (lanthanum oxide) accounts for 8% of the sum of the masses of the carrier and the first metal component.

[0077] Example 2

[0078] (1) 114 g of small-pore SB powder, 340 g of modified kaolin, 46 g of zirconium oxide, 10 g of sodium methyl cellulose and 400 g of zinc oxide powder were mixed evenly, 460 g of water and 57 g of nitric acid were added, and the mixture was squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 30 hours; then dried at 110° C. for 6 hours, and then calcined at 450° C. for 5 hours to obtain a first intermediate in the form of small balls;

[0079] (2) Weighing 389 g of nickel nitrate hexahydrate, adding 1700 g of water to prepare a first impregnation solution; placing the first intermediate in the first impregnation solution, and impregnating at 60° C. for 10 h; drying the obtained impregnation product at room temperature for 36 h, then drying at 90° C. for 8 h, and then calcining at 550° C. for 4 h to obtain a second intermediate in the form of small balls;

[0080] (3) Weigh 54 g of lanthanum nitrate and add 2000 g of water to prepare a second impregnation solution; place the second intermediate in the second impregnation solution and impregnate at 65° C. for 12 h; dry the obtained impregnation product at room temperature for 48 h, then dry it at 100° C. for 8 h, and then calcine it at 500° C. for 3 h to obtain a spherical third intermediate;

[0081] (4) Weigh 50 g of trifluoroacetic acid, add 1800 g of water to prepare a solution, place the third intermediate in the solution, and immerse it at 45° C. for 8 h; dry the obtained impregnation product at room temperature for 24 h, then dry it at 80° C. for 10 h, and then calcine it at 650° C. for 4 h to obtain an adsorbent precursor;

[0082] (5) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S1; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 350° C., reduction treatment time 2 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 100%;

[0083] Among them, the first metal component (zinc + nickel) and the second metal component (lanthanum) are both calculated as metal oxides, the mass of the first metal component accounts for 50% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 10% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (lanthanum oxide) accounts for 4% of the sum of the masses of the carrier and the first metal component.

[0084] Example 3

[0085] (1) 95 g of small-pore SB powder, 238 g of modified kaolin, 67 g of zirconium oxide, 30 g of sesbania powder and 550 g of zinc oxide powder were mixed evenly, 473 g of water and 66.5 g of nitric acid were added, and the mixture was mixed evenly and squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 36 hours; then dried at 90° C. for 10 hours, and then calcined at 450° C. for 3 hours to obtain a first intermediate in the form of small balls;

[0086] (2) Weighing 166.5 g of nickel acetate tetrahydrate, adding 2400 g of water to prepare a first impregnation solution; placing the first intermediate in the first impregnation solution, and impregnating at 60° C. for 10 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 100° C. for 8 h, and then calcining at 550° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0087] (3) Weigh 66.5 g of lanthanum nitrate and add 2500 g of water to prepare a second impregnation solution; place the second intermediate in the second impregnation solution and impregnate at 55° C. for 12 h; dry the obtained impregnation product at room temperature for 36 h, then dry it at 90° C. for 8 h, and then calcine it at 550° C. for 4 h to obtain a spherical third intermediate;

[0088] (4) Weigh 40 g of trifluoroacetic acid, add 1700 g of water to prepare a solution, place the third intermediate in the solution, and immerse it at 40° C. for 12 h; dry the obtained impregnation product at room temperature for 48 h, then dry it at 110° C. for 8 h, and then calcine it at 500° C. for 4 h to obtain an adsorbent precursor;

[0089] (5) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S3; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 350° C., reduction treatment time 4 h, hydrogen volume space velocity 2500 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 90%;

[0090] Among them, the first metal component (zinc + nickel) and the second metal component (lanthanum) are both calculated as metal oxides, the mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 5% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (lanthanum oxide) accounts for 5% of the sum of the masses of the carrier and the first metal component.

[0091] Example 4

[0092] (1) 92 g of small-pore SB powder, 138 g of modified kaolin, 70 g of zirconium oxide, 45 g of sodium methylcellulose and 620 g of zinc oxide powder were mixed evenly, 455 g of water and 55 g of nitric acid were added, and the mixture was mixed evenly and then extruded into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 18 hours; then dried at 110° C. for 10 hours, and then calcined at 550° C. for 3 hours to obtain a first intermediate in the form of small balls;

[0093] (2) Weighing 311 g of nickel nitrate hexahydrate, adding 3200 g of water to prepare a first impregnation solution; placing the first intermediate in the first impregnation solution, and impregnating at 55° C. for 8 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 100° C. for 8 h, and then calcining at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0094] (3) Weigh 93 g of lanthanum nitrate and add 3400 g of water to prepare a second impregnation solution; place the second intermediate in the second impregnation solution and impregnate at 45° C. for 12 h; dry the obtained impregnation product at room temperature for 48 h, then dry it at 80° C. for 10 h, and then calcine it at 600° C. for 3 h to obtain a spherical third intermediate;

[0095] (4) Weigh 30 g of trifluoroacetic acid, add 1920 g of water to prepare a solution, place the third intermediate in the solution, and immerse it at 60° C. for 6 h; dry the obtained impregnation product at room temperature for 24 h, then dry it at 110° C. for 6 h, and then calcine it at 550° C. for 3 h to obtain an adsorbent precursor;

[0096] (5) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S4; wherein the reduction treatment conditions are: pressure 0.5 MPa, temperature 450°C, reduction treatment time 2 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 70%;

[0097] Among them, the first metal component (zinc + nickel) and the second metal component (lanthanum) are both calculated as metal oxides, the mass of the first metal component accounts for 70% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 8% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (lanthanum oxide) accounts for 7% of the sum of the masses of the carrier and the first metal component.

[0098] Example 5

[0099] (1) 103 g of small-pore SB powder, 205 g of modified kaolin, 92 g of zirconium oxide, 50 g of sesbania powder and 540 g of zinc oxide powder were mixed evenly, 454 g of water and 82 g of nitric acid were added, and the mixture was mixed evenly and squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 24 hours, then dried at 100° C. for 6 hours, and then calcined at 500° C. for 3 hours to obtain a first spherical intermediate;

[0100] (2) Weigh 200 g of nickel acetate tetrahydrate and add 3000 g of water to prepare a first impregnation solution; place the first intermediate in the first impregnation solution and impregnate at 65° C. for 6 h; dry the obtained impregnation product at room temperature for 24 h, then dry it at 90° C. for 10 h, and then calcine it at 450° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0101] (3) Weigh 80 g of lanthanum nitrate and add 3000 g of water to prepare a second impregnation solution; place the second intermediate in the second impregnation solution and impregnate at 60° C. for 10 h; dry the obtained impregnation product at room temperature for 24 h, then dry it at 110° C. for 10 h, and then calcine it at 500° C. for 4 h to obtain a spherical third intermediate;

[0102] (4) Weigh 50 g of trifluoroacetic acid, add 1600 g of water to prepare a solution, place the third intermediate in the solution, and immerse at 55° C. for 10 h; dry the obtained impregnation product at room temperature for 36 hours, then dry at 100° C. for 10 hours, and then calcine at 450° C. for 4 hours to obtain an adsorbent precursor;

[0103] (5) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S5; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 450°C, reduction treatment time 3 h, hydrogen volume space velocity 3000 h -1, the volume fraction of hydrogen in the atmosphere containing hydrogen is 60%;

[0104] Among them, the first metal component (zinc + nickel) and the second metal component (lanthanum) are both calculated as metal oxides, the mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 6% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (lanthanum oxide) accounts for 6% of the sum of the masses of the carrier and the first metal component.

[0105] Example 6

[0106] (1) 83 g of small-pore SB powder, 167 g of modified kaolin, 50 g of zirconium oxide, 60 g of sodium carboxymethyl cellulose and 520 g of zinc oxide powder were mixed evenly, 420 g of water and 58 g of nitric acid were added, and the mixture was mixed evenly and then extruded into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 24 hours; then dried at 100° C. for 8 hours, and then calcined at 650° C. for 3 hours to obtain a first intermediate in the form of small balls;

[0107] (2) Weigh 272.5 g of nickel nitrate hexahydrate, add 2700 g of water to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 50° C. for 10 h; naturally dry the obtained impregnation product at room temperature for 48 hours; then dry at 800° C. for 8 hours, and then calcine at 600° C. for 3 hours to obtain a second intermediate in the form of small balls;

[0108] (3) Weigh 80 g of lanthanum nitrate and add 2000 g of water to prepare a second impregnation solution; place the second intermediate in the second impregnation solution and impregnate at 65° C. for 10 h; dry the obtained impregnation product at room temperature for 36 h, then dry it at 100° C. for 6 h, and then calcine it at 550° C. for 4 h to obtain a spherical third intermediate;

[0109] (4) Weigh 40 g of trifluoroacetic acid, add 1850 g of water to prepare a solution, place the third intermediate in the solution, and immerse at 45° C. for 12 h; dry the obtained impregnated product at room temperature for 48 hours, then dry at 100° C. for 8 hours, and then calcine at 500° C. for 3 hours to obtain an adsorbent precursor;

[0110] (5) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S6; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 70%;

[0111] Among them, the first metal component (zinc + nickel) and the second metal component (lanthanum) are both calculated as metal oxides. The mass of the first metal component accounts for 66% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 7.86% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (lanthanum oxide) accounts for 6.74% of the sum of the masses of the carrier and the first metal component.

[0112] Comparative Example 1 to Comparative Example 6

[0113] The difference between Comparative Example 1 and Example 3 is that the small-pore SB powder in step (2) is replaced by modified kaolin, and the other conditions are the same as those in Example 3, to obtain a desulfurization adsorbent D1.

[0114] The difference between Comparative Example 2 and Example 3 is that the modified kaolin in step (2) is replaced by small-pore SB powder, and the other conditions are the same as those in Example 3, to obtain a desulfurization adsorbent D2.

[0115] The difference between Comparative Example 3 and Example 3 is that the modified kaolin in step (2) is replaced by macroporous pseudo-boehmite (the pore volume of the macroporous pseudo-boehmite is 0.8 mL / g to 1.2 mL / g and the specific surface area is 280 m 2 / g~360m 2 / g), and the other conditions were the same as those in Example 3 to obtain desulfurization adsorbent D3.

[0116] The difference between Comparative Example 4 and Example 3 is that the zirconium oxide in step (2) is replaced by modified kaolin, and the other conditions are the same as those in Example 3, to obtain a desulfurization adsorbent D4.

[0117] The difference between Comparative Example 5 and Example 4 is that the zirconium oxide in step (2) is replaced by small-pore SB powder, and the other conditions are the same as those in Example 4, to obtain a desulfurization adsorbent D5.

[0118] The difference between Comparative Example 6 and Example 4 is that the trifluoroacetic acid modification process in step (4) is eliminated, that is, the third intermediate is directly used as the adsorbent precursor for the reduction treatment in step (5), and the other conditions are the same as those in Example 4 to obtain the desulfurization adsorbent D6.

[0119] Application Examples

[0120] The desulfurization process of this application example is as follows: 200g of adsorbent is loaded into a fixed bed reactor, and then a heavy oil raw material is introduced into the fixed bed reactor, and is contacted and reacted with the desulfurization adsorbent under a hydrogen atmosphere (i.e., a desulfurization reaction is performed), and a desulfurized oil product and a regenerated adsorbent are obtained respectively; wherein the heavy oil raw material has a sulfur content of 2.3wt%, a nitrogen content of 0.8wt%, and a viscosity of 486mm 2 / s vacuum residue, the desulfurization process conditions are: temperature 420 ° C, pressure 4MPa, heavy oil feed rate of 100g / h (heavy oil feed space velocity of 0.5h -1 ), hydrogen flow rate 35L / h (the volume ratio of hydrogen to heavy oil feedstock is 400:1).

[0121] S1-S6 and D1-D6 were used as desulfurization adsorbents to carry out the above desulfurization process, so as to evaluate the performance of S1-S6 and D1-D6. The crushing strength of adsorbents S1-S6 and D1-D6, as well as the desulfurization rate and denitrification rate achieved by each adsorbent, and the viscosity of the desulfurized oil obtained after the adsorption desulfurization of heavy oil raw materials by each adsorbent are shown in Tables 1 and 2, respectively.

[0122] Table 1 Adsorbent performance evaluation results

[0123] Desulfurization adsorbent S1 S2 S3 S4 S5 S6 Crushing strength / N 30 33 34 35 32 36 Desulfurization rate / % 83 81 82 84 80 81 Denitrification rate / % 52 55 57 54 58 53 <![CDATA[Viscosity of desulfurized oil / (mm 2 / s)]]> 324 358 349 367 386 335

[0124] Table 2 Adsorbent performance evaluation results

[0125] Desulfurization adsorbent D1 D2 D3 D4 D5 D6 Crushing strength / N 10 23 25 24 28 33 Desulfurization rate / % 80 65 73 80 82 79 Denitrification rate / % 38 40 36 43 41 5 <![CDATA[Viscosity of desulfurized oil / (mm 2 / s)]]> 298 543 539 413 389 376

[0126] It can be seen from Table 1 and Table 2 that S1 to S6 have good mechanical properties, and can improve the desulfurization rate, denitrification rate, and reduce the viscosity of heavy oil, thereby improving the quality of desulfurized oil products. Among them, the desulfurization adsorbent prepared by modifying the third intermediate with trifluoroacetic acid also has denitrification activity, which can make the denitrification rate reach more than 50%.

[0127] In addition, the adsorbent stability of S1~S6 and D1~D6 was evaluated, and the desulfurization activity of the adsorbent after different regeneration times was measured. The results showed that the desulfurization activity stability of S1~S6 was much better than that of D1~D6. Specifically, the desulfurization rate of the adsorbent after different regeneration times was measured according to the following desulfurization-regeneration process:

[0128] The above desulfurization process is carried out using unused fresh adsorbent to obtain desulfurized oil products and once-regenerated adsorbent, and the desulfurization rate of the fresh adsorbent is measured;

[0129] The regenerated adsorbent is regenerated according to the following regeneration process: the regenerated adsorbent is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 7%, and the volume space velocity of the oxygen-containing gas is 2000h -1The temperature of the oxidation regeneration is 350°C, the pressure of the oxidation regeneration is 0.5 MPa, and the time of the oxidation regeneration is 60 h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated catalyst (i.e., regenerated once); wherein the volume fraction of hydrogen in the atmosphere containing hydrogen is 75%, and the volume space velocity of hydrogen is 2000 h -1 , the temperature of the second reduction treatment is 400°C, the pressure of the second reduction treatment is 1.0MPa, and the time of the second reduction treatment is 4h;

[0130] The above desulfurization process is carried out using a once-regenerated adsorbent to obtain a desulfurized oil product and a second-time adsorbent to be regenerated, and the desulfurization rate of the once-regenerated adsorbent is measured; the second-time adsorbent to be regenerated is then regenerated according to the above regeneration process to obtain a second-time regenerated adsorbent (i.e., regenerated twice); the above desulfurization process is carried out using a second-time regenerated adsorbent to obtain a desulfurized oil product and a second-time adsorbent to be regenerated, and the desulfurization rate of the second-time regenerated adsorbent is measured… According to the above process, the desulfurization rates after the adsorbent is regenerated 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, and 60 times are measured respectively.

[0131] Taking S3, S4, D4 and D5 as examples, the desulfurization rates corresponding to different regeneration times measured according to the above process are shown in Table 3.

[0132] Table 3 Adsorbent stability evaluation results

[0133]

[0134] Note: After D4 and D5 were regenerated 20 times, the desulfurization rate dropped significantly and was not shown in Table 3.

[0135] It can be seen from Table 3 that after S3 and S4 were regenerated 60 times, they were still able to maintain a high desulfurization rate, which was basically equivalent to that of fresh desulfurization adsorbents, showing good desulfurization activity stability.

[0136] In addition, in order to further illustrate the performance difference between the desulfurization adsorbent prepared in the above embodiment and the desulfurization adsorbent prepared in the comparative example, taking S1, S2, D4, and D5 as examples, XRD analysis was performed on the adsorbent precursor in the preparation process (i.e., the product before the first reduction treatment) and the regenerated adsorbent precursor when the fifth regeneration was performed according to the above desulfurization-regeneration process (i.e., the product before the second reduction treatment), and the results are shown in FIG. Figure 1 and Figure 2 ,in, Figure 1The fresh agent S1 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent S1, the fresh agent S2 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent S2, the fresh agent D4 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent D4, and the fresh agent D5 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent D5; Figure 2 The regeneration agent S1 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent S1 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent S2 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent S2 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent D4 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent D4 is regenerated for the fifth time according to the above desulfurization-regeneration process, and the regeneration agent D5 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent D5 is regenerated for the fifth time according to the above desulfurization-regeneration process.

[0137] from Figure 1 and Figure 2 It can be seen that the main characteristic diffraction peaks in fresh agent S1, fresh agent S2, fresh agent D4 and fresh agent D5 are zinc oxide crystal phase peaks (2θ is 31.5°, 34.4° and 36.2°) and nickel oxide crystal phase peaks (2θ is 36.9° and 43.0°). The characteristic diffraction peak of ZnO is sharp and has high intensity, and it is the main active component. Compared with the fresh agent, the XRD spectra of the regenerated agent (i.e., regenerated agent S1, regenerated agent S2, regenerated agent D4 and regenerated agent D5) are Figure 2 ) is significantly more complex, including desulfurization products such as ZnS, ZnAl 2 O 4 、Zn 2 SiO 4 New phases are generated. Compared with regenerator S1, regenerator S2, regenerator D4 and regenerator D5, the intensities of the characteristic diffraction peaks of zinc aluminum spinel and zinc silicate are significantly enhanced in the XRD spectra.

[0138] The active ZnO in the desulfurization adsorbent continuously reacts with the aluminum source and silicon source in the carrier to generate inactive zinc aluminum spinel and zinc silicate, and zinc aluminum spinel and zinc silicate can no longer be converted into active ZnO during the regeneration process, indicating that they are difficult to regenerate, thereby forming inactive components, and due to their high content, the content of the active component ZnO in the desulfurization adsorbent will be greatly reduced, resulting in problems such as difficulty in sulfur transfer and insufficient sulfur storage capacity during adsorption desulfurization, affecting the desulfurization activity and other properties of the desulfurization adsorbent; at the same time, the generation of zinc aluminum spinel and zinc silicate will also destroy the carrier structure, resulting in a decrease in the strength of the desulfurization adsorbent, making the desulfurization adsorbent more easily broken and deteriorating its performance. Therefore, the above XRD analysis further illustrates that, relative to the desulfurization adsorbent prepared in the comparative example, the desulfurization adsorbent prepared in the embodiment has better desulfurization activity stability and mechanical strength and other properties.

[0139] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A desulfurization adsorbent, characterized in that: The invention comprises a carrier, a first metal component and a second metal component; wherein the first metal component comprises zinc oxide and nickel, the second metal component comprises lanthanum, the carrier is compounded from raw materials containing small-pore SB powder, modified kaolin and zirconium oxide, the pore volume of the small-pore SB powder is not greater than 0.8 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is subjected to a primary roasting at 900° C. to 1100° C., then subjected to alkali modification, then washed to neutrality, and then subjected to a secondary roasting at 500° C. to 600° C. to obtain the modified kaolin, wherein the alkali modification is used to extract silicon oxide from the kaolin; The desulfurization adsorbent is prepared by the following steps: (I) adding an inorganic acid and water to a mixture containing the small-pore SB powder, modified kaolin, zirconium oxide, a binder and zinc oxide, and then sequentially performing molding, drying and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a third intermediate; (IV) modifying the third intermediate with trifluoroacetic acid, and then drying and calcining to obtain an adsorbent precursor; (V) subjecting the adsorbent precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain the desulfurization adsorbent.

2. The desulfurization adsorbent according to claim 1, characterized in that: Calculated based on the oxide of the first metal component and the oxide of the second metal component, the following conditions are satisfied: The mass of the first metal component accounts for 50% to 80% of the sum of the mass of the carrier and the first metal component; and / or, The mass of nickel in the first metal component accounts for 3% to 12% of the sum of the mass of the carrier and the first metal component; and / or, The mass of the second metal component accounts for 0.5% to 8% of the sum of the masses of the carrier and the first metal component.

3. The desulfurization adsorbent according to claim 1, characterized in that: The mass ratio of the small-pore SB powder to the modified kaolin is 1:(1-3); and / or, The mass ratio of the zirconium oxide to the small-pore SB powder is (0.5-1):1; and / or, The pore volume of the small-pore SB powder is 0.4 mL / g to 0.8 mL / g, and the specific surface area is 180 m 2 / g~260m 2 / g, the peptization index is greater than 97%.

4. The desulfurization adsorbent according to claim 1 or 3, characterized in that: The time of the first calcination is 2h to 5h; and / or, The primary calcination temperature is 950°C to 1050°C; and / or, The alkali modification process comprises: immersing the kaolin raw material after the first roasting in an inorganic alkali solution for modification, wherein the mass concentration of the inorganic alkali solution is 5% to 20%, and the mass ratio of the inorganic alkali solution to the kaolin raw material is (2 to 4):1; the alkali modification time is 1h to 6h; and / or, The secondary calcination time is 2h to 5h.

5. The method for preparing the desulfurization adsorbent according to any one of claims 1 to 4, characterized in that: The binder comprises at least one of sodium methyl cellulose, sodium carboxymethyl starch, sodium carboxymethyl cellulose and sesbania powder; and / or, The nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 1% to 7% of the sum of the mass of the small-pore SB powder, modified kaolin, zirconium oxide, zinc oxide and the nickel compound; and / or, The mass ratio of the inorganic acid to the small-pore SB powder is (0.5-1):1; and / or, The zinc oxide comprises nano zinc oxide powder having a particle size not greater than 100 nm; and / or, The calcination conditions in step (I) are: calcination temperature of 400° C. to 700° C., calcination time of 1 h to 10 h; and / or, The calcination conditions in step (II) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, The calcination conditions in step (III) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, In step (IV), the process of modifying the third intermediate with trifluoroacetic acid comprises: impregnating the third intermediate with a solution containing the trifluoroacetic acid, wherein the mass ratio of the trifluoroacetic acid to the third intermediate is (0.01-0.1):1; and / or, The calcination conditions in step (IV) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, In step (V), the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h, wherein the pressure is a gauge pressure.

6. A method for desulfurization of sulfur-containing oil by hydrogenation adsorption, characterized in that: include: Desulfurization of sulfur-containing oil products using the desulfurization adsorbent according to any one of claims 1 to 4; or, The desulfurization adsorbent is prepared according to the preparation method of claim 5, and the desulfurization adsorbent is used to desulfurize sulfur-containing oil products.

7. The method for desulfurization of sulfur-containing oil by hydrogenation adsorption according to claim 6, characterized in that: The temperature of the desulfurization treatment is 300°C to 550°C; and / or, The desulfurization treatment pressure is 0.5 MPa to 10 MPa, and the pressure is a gauge pressure; and / or, The feed mass space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 and / or, The desulfurization treatment is carried out in a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):

1.

8. The method for desulfurization of sulfur-containing oil by hydrogenation adsorption according to claim 6, characterized in that: Also includes: After the desulfurization treatment, desulfurized oil products and adsorbent to be produced are obtained respectively; Regenerating the adsorbent to be regenerated to obtain a regenerated adsorbent; The regenerated adsorbent is returned to the desulfurization process; wherein the regeneration process comprises: The regenerated adsorbent is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , the temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5MPa, and the time of the oxidation regeneration is 20h to 100h, wherein the pressure is a gauge pressure; The regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated adsorbent; wherein the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300°C to 500°C, the pressure of the second reduction treatment is 0 to 3MPa, and the time of the second reduction treatment is 1h to 6h, wherein the pressure is a gauge pressure.

9. The method for desulfurization of sulfur-containing oil by hydrogenation adsorption according to claim 6, characterized in that: The sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

Citation Information

Patent Citations

  • Residual oil hydrogenation catalyst and preparation method and use thereof

    CN101491764A

  • Catalytic gasoline absorbing desulfurization catalyst, preparation method and application thereof

    CN101905161A

  • Active carbon used for adsorbing and removing sulfides in gasoline, and preparation method thereof

    CN102188954A

  • Preparation and application methods of adsorption desulfurization agent for upgrading of catalytically cracked gasoline

    CN103642520A

  • Fuel oil deep-adsorption desulfurizationn catalyst, preparation method and application thereof

    CN104056632A